Doses de fertilizantes potássicos no acúmulo de cloro e produção da cana-de-açúcar - Aloise, Gabriella Roquetti Guimarães (2018)
The high consumption of fertilizers used in sugar cane is due to its high nutritional needs as a function of the large biomass production per area and the high nutrient removal in the harvesting process. The use of potassic KCl fertilizer may be a factor that contributes indirectly to environmental pollution by emitting toxic chlorinated molecules from burning sugar cane biomass for the production of energy in ethanol and sugar industries. Knowledge of the sources of these molecules is important to determine the exposition risks for persons and other receptors and to establish alternatives for the control of these pollutants. This study evaluated the response of sugar cane treated with sources and doses of potassium fertilizers and investigated the accumulation of chlorine from KCl potassium fertilizer. In order to test the hypotheses of this study, two experiments were installed in the experimental area of the Institute of Agricultural Sciences of the Federal University of Uberlândia, at the Umuarama Campus in Uberlândia-MG, in 2016. The experimental unit of both experiments consisted of a 0.60-m diameter and 0.92-m high vase, filled with 200 kg of soil where three sugar cane seedlings, variety RB 93-7570, were planted. Both experiments were arranged in randomized blocks with four replicates. Experiment 1 consisted of a factorial (2x4 + 1), two potassium sources, KCl and K2SO4, four K2O doses (100, 200, 400, 800 kg ha-1) and one additional treatment without potassium sources. Sugarcane biometric variables did not present significant interactions, except for stalk average diameter. The variables fresh matter (FM), dry matter (DM) and fresh matter productivity (FMP) varied in function of K2O doses, which described quadratic mathematical models. In experiment 2, five doses of a K2O source consisting of the combination of two fertilizers (KCl + K2SO4) were applied in the following ratio (0 + 400, 100 + 300, 200 + 200, 300 + 100, 400 + 0 (kg ha-1) of K2O so that the concentration (of K2O) remained constant (400 kg ha-1) while the concentration of chloride varied. Chloride concentration in sugarcane biomass was adjusted to a quadratic mathematical model, which allowed the estimation of chloride accumulation in sugarcane biomass, in the 2017/2018 harvest, between 0.71 and 0.85 Mg.